Investigation of the characteristics of EUV backward transition radiation generated by 5.7 MeV electrons in mono- and multilayer targets; Journal of Physics: Conference Series; Volume 517, № 1 - Uglov S. R. Sergey Romanovich; Kaplin V. V.; Potylitsyn A. P. Alexander Petrovich; Sukhikh L. G. Leonid Grigorievich; Vukolov A. V.; Kube G. B. (2014, 2014)
This paper presents experimental results of a study of radiation in the vacuum ultraviolet and extreme ultraviolet spectral region, generated by electrons with an energy of 5.7 MeV in a multilayer X-ray mirror. The angular distribution of the radiation generated in the rear hemisphere from the input surface of the target was measured. The contribution to the radiation yield caused by the periodic structure of the multilayer target was experimentally investigated